HISTORICAL NARRATIVE: CONSTITUENT FEATURES AND LINGUISTIC PROPERTIES - Olga A. Leontovich; Anna A. Khanova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
While historians extensively research narrative and use a significant number of concepts that linguists traditionally see as their own, the properties of historical narrative have not received sufficient coverage in linguistics yet. This article analyses the similarities and differences in the approach to narrative by historians and linguists, formulates the linguistic criteria of narrativity and discusses the relationship between factuality and fictionality. The constitutive features of historical narrative identified and described in the present study include temporality, spatiality, eventfulness, informativeness, interpretability, ideologization and semioticity. Language is treated as a tool of verbalising historical narrative, structuring its chronology and logic, shaping the perception of events through a system of presuppositions, connotations, and allusions, creating historical ambiance and constructing mythologised designations. The linguistic means used in the construction of historical narrative comprise: 1) the language of the historical source; 2) the narrator’s language; 3) historical terminology; 4) historicisms and archaisms; 5) precedent names; 6) obsolete and modern toponyms. The study emphasises the importance of perceiving history as a hypertext – multiple narratives united by a network of intertextual connections. The study is illustrated by examples from narratives about the Silk Road in Chinese, Russian and English. The Silk Road symbolises the crossroads of civilisations, the interaction between East and West, the economic and cultural exchanges between Asia and Europe, peaceful cooperation, good neighbourliness, and shared cultural experience.